Terceiro setor, o diverso e a diversidade: o caso de uma organização recreativa. - Sousa, Liovalda da Silva (2017)
The main objective of this dissertation was to analyze how it has been during the last 10 years the administration of diversity in a recreational social club. To achieve this goal, a research was carried out to understand the third sector, as a niche where social clubs and diversity are found, as a differentiating element of this work. Bibliographical research on diversity was done; Third sector and organizational management in the third sector, aiming to obtain a better understanding of the theme; Research research in the organizational context of the Pica Pau Country Club; Field research consisting of phases of recognition and observation, conversations and data collection and definition of strategies for interviewing, and a case study, which was the last phase of the study. The results of the study indicate that in the past 10 years there has been an attempt to manage diversity in the club, but this was much more by legal determination than by managers' initiative or questioning and suggestion of members. The realization of the present study allowed to identify the changes, directed to the management of the diversities, that occurred in the club; Describe the position and vision of the members regarding changes and what they believe should occur and present suggestions for complementary actions for the management of the club and the diversity found during the course of management.